Rare Case of Rapidly Worsening REM Sleep Induced Bradycardia - Ayyappa S. Duba; Suneetha Jasty; Ankit Mahajan; Vijay Kodadhala; Raza Khan; Prithviraj Rai; Mohammad Ghazvini (Case Reports in Cardiology)
Sinoatrial arrest also known as sinus pause occurs when sinoatrial node of the heart transiently ceases to generate the electrical impulse necessary for the myocardium to contract. It may last from 2.0 seconds to several minutes. Etiologies of sinoatrial arrest can be complex and heterogeneous. During rapid eye movement (REM) sleep, sinus arrests unrelated to apnea or hypopnea are very rare and only a few cases have been reported. Here we report a case of 36-year-old male with no significant past medical history who presented to our hospital after a syncopal episode at night. Physical examination showed no cardiac or neurological abnormalities and initial EKG and neuroimaging were normal. Overnight telemonitor recorded several episodes of bradyarrhythmia with sinus arrest that progressively lengthened over time. Sleep study was done which confirmed that sinus arrests occurred more during REM sleep and are unrelated to apnea or hypopnea. Electrophysiology studies showed sinus nodal dysfunction with no junctional escape, subsequently a dual chamber pacemaker placed for rapidly worsening case of REM sleep induced bradycardia.